Value-based dimensions of national ethos among Malaysian university students - Ismail, Mohd Mahadee; Hassan, Nor Azlili; Abdullah, Nor Hafizah (Human Resource Management Academic Research Society, 2022)
University students are expected to hold views of harmony, bridge the ethnic differences and promote social cohesion which is central to the stability of a nation. There are shared values in the society that can unite individuals and groups together to promote the national ethos among the diverse ethnic citizens. This paper assumed that shared values played an important role in influencing the development of a conscious shared collective social bonding and encouraged a strong national ethos among Malaysian students. As university students play important roles in further developing the country economically and politically, it is very appropriate to study the levels of national ethos among Malaysian students. A total of 514 students from 14 public and private universities of various ethnic groups participated in a national survey using a self-administered questionnaire. Two dimensions of the national ethos emerged from the data, namely nationality, and patriotism, and the students hold positive perceptions of selected values of the country. However, there are differences among the various ethnic groups in their degree of attachment to the two dimensions of the national ethos studied. Overall, the value dimension has a positive and significant relationship and saw the flowering of national ethos among them.